THE INTEGRATION OF PARENTING THEORY, SELF-HEALING, AND STRUCTURAL THERAPY IN PARENTING EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Desri Jumiarti; Hapsah Md Yusof (LP2M Universitas Adzkia, 2025)
This study aims to develop a conceptual framework for parent education through the integration of parenting style theory, the self-healing approach, and Structural Family Therapy. The study addresses the fragmentation of existing parent education programs, which largely emphasize cognitive and behavioral aspects while overlooking affective and relational family dimensions. Using a pragmatist paradigm and an integrative literature review, this study synthesized interdisciplinary literature published between 2013 and 2024. Data were analyzed through open coding and thematic synthesis using ATLAS.ti and NVivo. The findings produced a reflective–transformative parent education model comprising four dimensions: affection (emotional healing and regulation), structure (family roles and boundaries), cognition (understanding authoritative parenting), and relations (parent–child communication and attachment). The model promotes a transdisciplinary, pragmatic, and restorative approach to parent education and provides a foundation for developing family policies, training modules, and community-based interventions.